Análisis de la pesca española en el Atlántico noreste 1980-2012: Papel de Galicia en la explotación de las principales especies marinas (Revista de Biología Marina y Oceanografía, 2019)
The Spanish fishing fleet is one of the most important in the European Union and is exploiting marine resources in the FAO area 27 (North-eastern Atlantic Ocean). The Galician Region has a relevant role in the fishing industry. The number of boats decreased significantly between 1980 and 2012. But the landing quantities of the main marine species exploited (small pelagic fishes and tuna species mainly) decreased faster that the fleet during the same period. In contrast, landing quantities of Elasmobranchs (sharks and rays) and Cephalopods increased. This analysis shows the overexploitation of the Atlantic fishing grounds.